WEB-орієнтований Internet-сервіс Wikipedia як засіб ведення інформаційної війни - Сокорчук, І. П. (ХНУРЭ, 2017)
This article examines the place of Web-service Wikipedia in carrying out of hybrid war. The author considers negative phenomena that take place on Wikipedia today. These problems related to principles of administration and maintenance of Wikipedia what do not provides its correct functioning in the conditions of information warfare. The author points to concrete facts from Wikipedia, showing the traits that are characteristic of a hybrid war. These facts indicate that the aggressor actively use Wikipedia as a component of the information war. The author proposed to solve this problem by using the Web encyclopedic resource that represents the real situation and devoid of these shortcomings of Wikipedia.
Матеріали ХХІ міжнародного молодіжного форуму "Рідіоелектроніка та молодь у ХХІ столітті"
Матеріали ХХІ міжнародного молодіжного форуму "Рідіоелектроніка та молодь у ХХІ столітті"
Keywords: Wikipedia; Hybrid War